Demise of cadaveric islet transplantation in the USA: Quo Vadis, 1 year after BLA approval and 24 years after the Edmonton breakthrough? - Witkowski, Piotr; Wojcik, Nicole; Appelbaum, Nathan; Fung, John J.; Barth, Rolf N.; Ricordi, Camillo (Frontiers in Transplantation, 2025)
More than a year after the Biological License Application (BLA) approval for CellTrans, cadaveric islet transplantation remains in demise in the United States (U.S.). While the therapy is unavailable to Americans, it is already a standard of care procedure in other countries, including Canada, Australia, and many in Europe. This article discusses the challenges stemming from an outdated regulatory framework in the U.S. concerning cadaveric islet transplantation. It also presents advocacy efforts by the transplant community for appropriate regulatory adjustments and discusses future perspectives.